HUBUNGAN ANTARA KEKETATAN RESPONS KEBIJAKAN PEMERINTAH DENGAN TREN KASUS KONFIRMASI COVID-19 DI INDONESIA - Hode, Meyga; Kandou, Grace D.; Mantjoro, Eva M. (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2023)
One of the diseases that is still priority of the world is COVID-19. The disease called pandemic since 2020 by WHO has developed to several new variants are found until November 2021 such as alpha, beta to delta variants. There is no indication for the end of this pandemic, so planning is needed until a response from the government is needed. The government's policy response has contributing to overcoming the pandemic of COVID-19. The Indonesian state, especially its government, is included in one of the countries with governments that have responded to the pandemic and issued various regulations and policies, but still experienced 2x the spike in cases until reports of public non-compliance with one of the health protocols were found. Based on this, it shows the leeway of various policies and regulations issued by the Indonesian government. This study plans to analyze new cases of confirmation with the stringency index of the government's policy response to COVID-19 cases in Indonesia. This research using observational analytical methods and cross sectional approaches has data sources originating from the ourworldindata.org website with a location in Indonesia for the period 2 March 2020 - 28 February 2022. Analysis with value ? = 0.05 using the spearman correlation test as a bivariate analysis test. The outcome of the study reveal p - value 0.000 and value r of 0.369. The conclusion is that there is a connection between the stringency of the government's policy response to COVID-19 and confirmed cases of COVID-19 in Indonesia.